Implementasi Kebijakan Sistem Zonasi - Desri Nora (Jurnal Ecogen, 2022)
This study aims to determine efforts to equalize the quality of education through zoning programs. This research is a literature study that discusses school zoning programs as an effort to equalize education. One of the efforts in equitable distribution of education carried out by the government is the school zoning program. Research using a literature approach, literature study is any effort made by researchers to collect information that is relevant to the topic or problem that will or is being studied. The results of this study show that 1) There are positive and negative impacts on the implementation of the zoning system, 2) Causes of Problems in the Zoning System Policy 3) Solutions to the Problems of the PPDB Zoning System